Interleukin 1 inhibits contraction of vascular smooth muscle. - Beasley, D (1989)
Interleukin 1 has been implicated as a mediator of both systemic and local responses to infection and injury. Since systemic and local vasodilatation are hallmarks of sepsis and infection, we studied the direct effect of IL-1 on vascular contractility. We report here that human recombinant IL-1-beta potently inhibits the response of rat thoracic aorta to vasoconstrictor agents. Exposure of isolated rat aortic rings to IL-1 (20 ng/ml) for 1 h did not affect phenylephrine-induced contractions during the exposure period. However, when rings were retested 150-200 min after initiation of IL-1 exposure, contractions were markedly decreased. The cytokine had a similar effect in rings from which the endothelium was removed. Contractions caused by potassium depolarization also were depressed, indicating the effect of IL-1 is not specific to the alpha-adrenoceptor agonist. The inhibitory effect of IL-1 was concentration-dependent (0.2 to 20 ng/ml), and eliminated by pretreatment with cycloheximide (20 micrograms/ml). Indomethacin (10(-5) M) did not prevent the inhibition caused by IL-1. These studies identify IL-1 as a potent inhibitor of vascular contraction, via an endothelium-independent mechanism. Studies with inhibitors suggest that the action of IL-1 is independent of prostanoid synthesis, and may involve synthesis of protein.